Preferensi Pemilihan Daerah Tujuan Wisata oleh Wisatawan Masa Pandemi Covid-19 di Jawa Barat - Hendra Gunawan; Sugiarti Rachim (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2022)
The Coronavirus desease-19 pandemic since the beginning of 2020 has had a negative impact on the tourism sector, not only reducing the number of visits but also changing the trend of choice of tourist destinations.  This study aims to assess people's preferences towards tourist destinations during the pandemic.  A survey using a questionnaire was conducted on 90 visitors to the National Flower and Animal Love Day exhibition at the Bogor Botanical Garden. The results of the study found that natural tourism became a trend during the pandemic, reaching 48.9% with the main objective of enjoying a pristine environment, a quiet and calm atmosphere, and cool and fresh air.  Botanical gardens have the highest selection index for residents over the age of 50, while zoos, safari parks, national parks and natural parks have the highest selection index for the age group of adolescents to 20 years.  Zoos and safari parks were favored by informants from the city, botanical gardens were favored by informants from the village, while national parks and natural parks were favored by both.  Extreme tourism activities are preferred by the 31–40-year age group, moderate activities are preferred by the 41–50-year age group, while special interest tourism is preferred by the age group of 50 years and over.  There is a trend of male informants liking natural tourism and modern tourism, while female informants like cultural, culinary and religious tourism.  Due to changes in preferences for selecting tourist destinations and types of tourist activities, tourism managers are advised to carry out various product innovations or tour packages, visitor services, promotion/marketing, improve visitor facilities adapted to new normal conditions, and continue to implement health protocols.